PROVISION OF EDUCATION AND ASSISTANCE TO PREVENT COVID-19FOR CITIZENS ALALAK ISLAND VILLAGE OF THE BARITO KUALA REGENCY - Yenny Okvitasari (UMBanjarmasin, 2021)
The COVID-19 pandemic caused by the coronavirus (SARS-Cov-2) continues to change world health, and the global transmission rate has reached the level that one infected person can only infect another. Dedicated community members are located in densely populated areas and have insufficient adherence to hygiene procedures, which makes it easy to spread. Seeing this situation, it is very important for community members to have dedication to protect themselves and their families from contracting COVID-19. Therefore, the team carried out education in a spirit of dedication to increase the knowledge of the community so that they can face and pass the COVID-19 pandemic, and the team also provided COVID-19 prevention assistance to overcome the limited prevention means in the community. community.